Clinical Data Combined With Modeling and Simulation Indicate Unchanged Drug‐Drug Interaction Magnitudes in the Elderly. Issue 2 (18th September 2020) - Stader, Felix; Courlet, Perrine; Kinvig, Hannah; Penny, Melissa A.; Decosterd, Laurent A.; Battegay, Manuel; Siccardi, Marco; Marzolini, Catia
Abstract : Age‐related comorbidities and consequently polypharmacy are highly prevalent in the elderly, resulting in an increased risk for drug‐drug interactions (DDIs). The effect of aging on DDI magnitudes is mostly uncertain, leading to missing guidance regarding the clinical DDI management in the elderly. Clinical data obtained in aging people living with HIV ≥ 55 years, who participated in the Swiss HIV Cohort Study, demonstrated unchanged DDI magnitudes with advanced aging for four studied DDI scenarios. These data plus published data for midazolam in the presence of clarithromycin and rifampicin in elderly individuals assessed the predictive potential of the used physiologically‐based pharmacokinetic (PBPK) model to simulate DDIs in the elderly. All clinically observed data were generally predicted within the 95% confidence interval of the PBPK simulations. The verified model predicted subsequently the magnitude of 50 DDIs across adulthood (20–99 years) with 42 scenarios being only verified in adults aged 20–50 years in the absence of clinically observed data in the elderly. DDI magnitudes were not impacted by aging regardless of the involved drugs, DDI mechanism, mediators of DDIs, or the sex of the investigated individuals. The prediction of unchanged DDI magnitudes with advanced aging were proofed by 17 published, independent DDIs that were investigated in young and elderly subjects. In conclusion, this study demonstrated by combining clinically observed data with modeling and simulation that aging does not impact DDI magnitudes and thus, clinical management of DDIs can a priori be similar in aging men and women in the absence of severe comorbidities.